WNT/β‐catenin signal inhibitor IC‐2–derived small‐molecule compounds suppress TGF‐β1–induced fibrogenic response of renal epithelial cells by inhibiting SMAD2/3 signalling. (12th February 2020) - Hoi, Shotaro; Tsuchiya, Hiroyuki; Itaba, Noriko; Suzuki, Kyosuke; Oka, Hiroyuki; Morimoto, Minoru; Takata, Tomoaki; Isomoto, Hajime; Shiota, Goshi
Abstract: Renal fibrosis compromises kidney function, and it is a risk factor for chronic kidney disease (CKD). CKD ultimately progresses to end‐stage kidney disease that can be cured only by kidney transplantation. Owing to the increasing number of CKD patients, effective treatment strategies are urgently required for renal fibrosis. TGF‐β is a well‐established fibrogenic factor that signals through SMAD2/3 signaling pathway. It was shown that there is a cross‐talk between TGF‐β/SMAD and WNT/β‐catenin signaling pathways in renal tubular epithelial cells, and that a WNT/β‐catenin inhibitor, ICG‐001, ameliorates TGF‐β1induced renal fibrosis. IC‐2, a derivative of ICG‐001, has been shown to potently induce hepatocyte differentiation of human mesenchymal stem cells by inhibiting WNT/β‐catenin signaling. In the present study, we examined the effect of ICG‐001, IC‐2, and IC‐2 derivatives (IC‐2‐506‐1, IC‐2‐506‐2, IC‐2‐506‐3, IC‐2‐Ar‐Cl, IC‐2‐OH, IC‐2‐OTBS, and IC‐2‐F) on TGF‐β1–induced SMAD activation and fibrogenic response in immortalized human renal tubular epithelial HK‐2 cells. All these compounds inhibited LiCl‐induced WNT/β‐catenin reporter activation to a similar extent, whereas ICG‐001, IC‐2‐OTBS, and IC‐2‐F almost completely suppressed TGF‐β1–induced SMAD reporter activation without apparent cytotoxicity. Phosphorylation of SMAD2/3 by TGF‐β1 was more potently inhibited by IC‐2‐OTBS and IC‐2‐F than by ICG‐001 and IC‐2. IC‐2‐F suppressed TGF‐β1–induced COL1A1 protein expression, whereas IC‐2‐506‐1 and IC‐2‐OTBS suppressed TGF‐β1–induced epithelial‐mesenchymal transition. These results demonstrated that IC‐2 derivatives suppress the TGF‐β1–induced fibrogenic response of tubular epithelial cells and thus could be promising therapeutic agents for the treatment of renal fibrosis.